(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The study’s objectives are to determine the prevalence of Entamoeba species in Waist Province’s farm animals and children. 80 Stool samples were collected from villager children (1-6 years) whom attended to (Al –kut Hospital for Gyneclogy and obstetrics and pediatrics) and 75 Stool samples from farm animals ( 25 Sheep, 25 cattle, and 25 goats ) . In children the results were revealed that 45(56.2%) which infection with Entamoeba spp. The age group of 3–4 years had the highest infection rate (87.5%), whereas the age group of 1-3 years had the lowest infection rate (26.66%). A statistical examination of the data revealed five Entamoeba species and a significant variance (P<0.05) in the total prevalence of these species among child groups. E. disper, E. moshkovskii, E. polecki, E. hartmanni, and E. histolytica were found in samples of feces. Three farm animals in Waist Province had an overall prevalence of 84% (75/63) Entamoeba spp., with infection rates varying from 72% to 100% for various animals and Entamoeba species. Three species were identified: E. bovis, E. moshkovskii, and E. histolytica. The findings gave insight into the extent of animal infections with Entamoeba spp. in Waist Province and emphasized the pressing necessity to put preventative measures in place to shield humans from this zoonotic illness.